Contributions to the study on different parameters of the carpathian lynx (Lynx lynx ssp. carpathicus) skulls from Romania - Georgescu, Bogdan; Predoi, Gabriel; Roșu, Petronela-Mihaela; Raita, Ștefania-Mariana; Bărbuceanu, Florica; Ghimpețeanu, Oana-Mărgărita; Ciobanu, Marius-Mihai; Vișoiu, C.; Petrescu, C. (”Ion Ionescu de la Brad” University of Agricultural Sciences and Veterinary Medicine, Iași, 2016)
This species is not included on the I.U.C.N. Red List, but in Romania, due to the relative high number of individuals, it is considered to be a protected species by governmental acts. During certain periods, in exchange of a tax, hunting is accepted for a limited number of individuals. Five skulls of Eurasian lynx, owned by the Department of Anatomy Museum of the Faculty of Veterinary Medicine of Bucharest, were morphometrically examined. The dimensions of the five skulls were compared with the literature in order to fit into the subspecies called Carpathian lynx (Lynx lynx ssp. carpathicus). Cranial measurements were performed using electronic digital calipers reading a tenth of a millimeter. Cranial measurements were compared with those made by Angela von den Driesch (1976). Generally, it was observed that the results regarding the dimensions of the skulls can be compared with the results obtained by G.E. Predoiu (2011). But there are four parameters, maximum width of the skull between the orbits, the width of the canine teeth socket, maximum length of skull and length of the mandible, larger than the subspecies described by G.E. Predoiu. These dimensional differences can be explained by the fact that some of the 5 skulls from the Anatomy Department belonged to an outstanding specimen. The C.I.C. score (the value of trophy hunting that can be awarded) for 4 of the 5 studied cases show that the skulls belonged to an outstanding specimen with Gold Medal.